Workplace conflict affecting team performance in advertising industry at Klang Valley - Chong, Mei Poh; Chang, Lee Yee; Lee, Jiann Woei; Ong, Yun Ru; Tay, Cher Hui (2011)
Given the rise in application of teams and teaming worldwide, organizations are placing greater reliance on these teams to maintain competitiveness, further improve effectiveness and efficiency, achieve competitive advantage, and ensure sustainability in this rapidly changing environment. Therefore, enhancing team effectiveness and performance has become a significant matter to prevailing organizations. This study is about “Workplace Conflict Affecting Team Performance in Advertising Industry within Klang Valley”. Our main goal for this study is to determine types of workplace conflict which could be found within teams in an organization. Other than that, the relationship between workplace conflict and team performance is examined as well. Workplace conflicts identified include task conflict, relationship conflict, process conflict, intra-group conflict and intergroup conflict. A total of 150 sets of questionnaires were distributed to workforce involved in advertising industry within Klang Valley, Malaysia. As a result, it is proven that there is a positive relationship between task conflict, intra-group conflict, intergroup conflict and team performance. As for relationship conflict and process conflict, a negative relationship is examined as well.